THERMODYNAMIC EVALUATION OF EDUCATION ALUMINATES, BORATES AND ALKALI METAL ALUMINOSILICATE - , В. А., Р. Д., Е. В., А. С. (Municipal economy of cities. Series: «Economy science», 2013)
This article describes the results of thermodynamic analysis of reactions of lithium-contain coating with a surface layer of aluminum-boric-silicate glass.